A Study of Investment Awareness and Preference of Individuals Toward Various Mutual Fund Schemes with Reference to Islampur City - Mr. Shekhar M. Gidde; Dr. Hemlata Gaikwad (International Journal of Research and Applied Technology (INJURATECH), 2022)
Mutual fund is an investment option which includes bonds, stock or securities used by the professional money managers. Investment is done for earning the regular and risk free returns from investment. In our country number of investment options are available, they are ranging from insurance policies to stocks. The study aims at finding the awareness of individuals towards mutual fund and preferences toward it. In our study it is found that the more number of respondents are aware about mutual fund. Investors purchase funds from brokers and asset management companies in large numbers. The majority of respondents are satisfied with mutual fund investment